2013
DOI: 10.5704/moj.1303.018
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Surgical Treatment of Pelvic Osteosarcoma: Hospital Universiti Sains Malaysia Experience

Abstract: We reviewed the surgical treatment and outcomes of 13 patients with pelvic osteosarcoma treated in our centre in the past decade. The study sample included 9 males and 4 females with a mean age of 28.1 years. Four patients had ileal lesions, five had acetabulum lesions, one had a ischiopubis lesion, and three had involvement of the whole hemipelvis. Seven patients presented with distant metastases at diagnosis. Limb salvage was performed in 6 patients and amputation in 7. In 60% of cases in the limb salvage su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…An epidemiological study conducted in Pakistan in 2010 showed a similar prevalence of different bone sarcomas as shown in the international literature, but it did not address site-specific prevalence, and therefore the possibility of a different prevalence pattern for pelvic tumors in Pakistan compared with the western world cannot be excluded 14 . The mean follow-up period was comparable to that of other studies, but it was noted that around 21% of the patients were lost to follow-up 7 , 15 . In our setting, most of the patients belong to lower socioeconomic classes and also come from distant places, and hence financial constraints and inadequate transportation could be the possible causes of loss to follow-up.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…An epidemiological study conducted in Pakistan in 2010 showed a similar prevalence of different bone sarcomas as shown in the international literature, but it did not address site-specific prevalence, and therefore the possibility of a different prevalence pattern for pelvic tumors in Pakistan compared with the western world cannot be excluded 14 . The mean follow-up period was comparable to that of other studies, but it was noted that around 21% of the patients were lost to follow-up 7 , 15 . In our setting, most of the patients belong to lower socioeconomic classes and also come from distant places, and hence financial constraints and inadequate transportation could be the possible causes of loss to follow-up.…”
Section: Discussionsupporting
confidence: 81%
“…These tumors also tend to present late and therefore pose a major challenge for orthopedic oncologists because of the large tumor size, local extension, and complex anatomy with proximity to major neurovascular structures and intestinal and urinary tracts. Subsequently, these are also associated with less favorable outcomes in terms of prognosis and survival compared with other extremity tumors 2 , 5 7 .…”
mentioning
confidence: 99%
“…Major pelvic resections have been classified by the Musculoskeletal Tumor Society into 3 resection types: type I (iliac), type II (periacetabular), and type III (obturator). Resections that involving the sacrum are type IV resections, or combinations thereof, based on the system established by Enneking and Dunham [18] , [22] , [23] . Pelvic resections that include the femoral head have been designated as type H and are classified into 3 types: type H1 (femoral head), type H2 (pertrochanteric area), and type H3 (subtrochanteric area) as in this patient we performed type H1–2 resections of proximal femur because the plan was to do a reconstruction using total hip replacement, and also the proximal femur used for an autograft parts of the reconstruction [24] .…”
Section: Discussionmentioning
confidence: 99%